2020
DOI: 10.1111/dom.14082
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐glucose co‐transporter‐2 inhibitors and the risk of urosepsis: A multi‐site, prevalent new‐user cohort study

Abstract: Short running title "SGLT2i and urosepsis" Word Count: 3475; Abstract Word Count: 249, Number of references 40, Number of tables 3, Number of figures 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
0
15
0
3
Order By: Relevance
“…However, a meta-analysis and two cohort studies all reported no increase in risk for UTI. 12 14 Rather, SGLT2i use has been associated with increased glucosuria and risk for genital mycotic infections. 11 , 12 , 20 22 When compared with DPP-4i initiation, SGLT2i use was associated with increased risk for genital mycotic infection without an increased risk for UTI in older adults, though events were still rare.…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis and two cohort studies all reported no increase in risk for UTI. 12 14 Rather, SGLT2i use has been associated with increased glucosuria and risk for genital mycotic infections. 11 , 12 , 20 22 When compared with DPP-4i initiation, SGLT2i use was associated with increased risk for genital mycotic infection without an increased risk for UTI in older adults, though events were still rare.…”
Section: Discussionmentioning
confidence: 99%
“…Data were from an existing multi-database retrospective cohort study conducted by the Canadian Network for Observational Drug Effect Studies (CNODES) [ 12 ], a pan-Canadian network that examines questions of drug safety and effectiveness at the request of government stakeholders. This cohort study investigated the safety and effectiveness of sodium-glucose cotransporter-2 (SGLT2) inhibitors, a new class of antidiabetic medications, compared to dipeptidyl peptidase-4 (DPP-4) inhibitors [ 13 16 ]. Databases from five Canadian provinces (Alberta, British Columbia, Manitoba, Ontario, and Quebec) and the United Kingdom (UK) Clinical Practice Research Datalink (CPRD) were used.…”
Section: Methodsmentioning
confidence: 99%
“…The cohort has been described in detail elsewhere [ 13 16 ]. Briefly, the cohort for the initial multi-database study included patients who received a prescription for a SGLT2 inhibitor or a DPP-4 inhibitor.…”
Section: Methodsmentioning
confidence: 99%
“…[25], Urologen oft nicht an der Therapie weiblicher FG Patienten beteiligt sind [26], Candida species oft in den Wunden der FG Patienten nachgewiesen werden, sodass eine primäre antimykotische Therapie evaluiert werden sollte [27] und dass die hyperbare Oxygenierung (HBO) als auch der vakuum-assistierte Wundverschluss (VAC) positive Effekte auf die Behandlungsergebnisse haben [28,32]. Die oben angesprochene Kohortenstudie konnte ebenfalls kein erhöhtes Risiko für FG bei der Einnahme von SGLT2-und DPP4-Hemmern (Antidiabetika) nachweisen [31].…”
Section: Ergebnisse Aus Den Retrospektiven Studienunclassified
“…Mit diesem Fakt beschäftigen sich insgesamt 4 der inkludierten Arbeiten. Zusammenfassend konnte in allen Studien kein signifikanter Zusammenhang mit diesen Antidiabetika aufgezeigt werden [31,36,37,41]. [38].…”
Section: Ergebnisse Des Systematischen Reviewsunclassified